T cell interaction with activated endothelial cells primes for tissue-residency - Wienke, Judith; Veldkamp, Saskia R.; Struijf, Eva M.; Yousef Yengej, Fjodor A.; van der Wal, M. Marlot; van Royen-Kerkhof, Annet; van Wijk, Femke (Frontiers in Immunology, 2022)
Tissue-resident memory T cells (TRM) are suspected drivers of chronic inflammation, but their induction remains unclear. Since endothelial cells (EC) are obligate interaction partners for T cells trafficking into inflamed tissues, they may play a role in TRM development. Here, we used an in vitro co-culture system of human cytokine-activated EC and FACS-sorted T cells to study the effect of EC on T(RM) cell differentiation. T cell phenotypes were assessed by flow cytometry, including proliferation measured by CellTrace Violet dilution assay. Soluble mediators were analyzed by multiplex immunoassay. Co-culture of T cells with cytokine-activated, but not resting EC induced CD69 expression without activation (CD25, Ki67) or proliferation. The dynamic of CD69 expression induced by EC was distinct from that induced by TCR triggering, with rapid induction and stable expression over 7 days. CD69 induction by activated EC was higher in memory than naive T cells, and most pronounced in CD8+ effector memory T cells. Early CD69 induction was mostly mediated by IL-15, whereas later effects were also mediated by interactions with ICAM-1 and/or VCAM-1. CD69+ T cells displayed a phenotype associated with tissue-residency, with increased CD49a, CD103, CXCR6, PD-1 and CD57 expression, and decreased CD62L and S1PR1. EC-induced CD69+ T cells were poised for high production of pro-inflammatory cytokines and showed increased expression of T-helper 1 transcription factor T-bet. Our findings demonstrate that activated EC can induce functional specialization in T cells with sustained CD69 expression, increased cytokine response and a phenotypic profile reminiscent of TRM. Interaction with activated EC during transmigration into (inflamed) tissues thus contributes to TRM-residency priming.